Insights into the epigenetics of chronic rhinosinusitis with and without nasal polyps: a systematic review - Brar, Tripti; Marks, Lisa; Lal, Devyani (Frontiers in Allergy, 2023)
Background: Epigenetics facilitates insights on the impact of host environment on the genesis of chronic rhinosinusitis (CRS), through modulations of host gene expression and activity. Epigenetic mechanisms such as DNA methylation cause reversible, but heritable changes in gene expression over generations of progeny, without altering the DNA base-pair sequences. These studies offer a critical understanding of environment-induced changes that result in host predisposition to disease and may help in developing novel biomarkers and therapeutics. The goal of this systematic review is to summarize the current evidence on epigenetics of CRS with a focus on CRSwNP, and highlight gaps that merit further research. Methods: A systematic review of the English language literature was performed to identify investigations related to epigenetic studies in subjects with CRSwNP. Results: The review identified 65 studies. These have focussed on DNA methylation and non-coding RNAs, with only a few on histone deacetylation, alternative polyadenylation (APA) and chromatin accessibility. Studies include those investigating in-vivo changes, in-vitro changes or both. Studies also include animal models of CRS. Almost all have been conducted in Asia. DNA methylation studies that were genome-wide found differences in global methylation between CRSwNP and controls, while others specifically found significant differences in methylation of CpG sites of TSLP, IL-8 and PLAT. In addition, DNA Methyltransferase inhibitors and Histone deacetylase inhibitors were studied as potential therapeutic agents. Majority studies investigating non-coding RNAs focussed on micro-RNAs and found differences in global expression of miRNA levels and also revealed some previously known, as well as novel targets and pathways like TNF alpha, TGF beta-1, IL-10, EGR2, AHR, PI3/AKT pathway, mucin secretion, vascular permeability. Overall, studies have found dysregulation in pathways/genes involving inflammation, immune regulation, tissue remodeling, structural proteins, mucin secretion, arachidonic acid metabolism and transcription. Conclusions: Epigenetic studies in CRS subjects suggest that there is likely a major impact of the environment. However, these are association studies and do not directly imply pathogenesis. Longitudinal studies in geographically and racially diverse population cohorts are necessary to quantify genetic versus environmental risks for CRSwNP and CRSsNP and assess heritability risk, as well as develop novel biomarkers and therapeutic agents.